Boosting Entrepreneurial Drive: The Impact of Motivation and Social Environment on Business Intentions - Fadhli Ahmad Fauzan; Nor Norisanti; Sopyan Saori (Edueksos: Jurnal Pendidikan Sosial & Ekonomi, 2024)
This study aims to analyze in depth the influence of motivation and social environment on entrepreneurial interest in Madrasah Aliyah Al Jazuliyah. Motivation and social environment have been identified as key factors that influence the tendency of individuals to start and run their businesses. This research uses descriptive and associative methods with a quantitative approach. The sampling technique in this study used a non-probability sampling technique of saturated sampling type, with a total sample of 117 students of Madrasah Aliyah Al Jazuliyah as respondents. Semantic differential is used as a scale, and the data analysis techniques used in this study are classical tests, multiple correlation coefficients, determination coefficients, multiple linear regression, and simultaneous hypothesis testing (F test) and partially (T test). The results in this study indicate that motivation has a significant effect on the entrepreneurial interest of active students of Madrasah Aliyah Al Jazuliyah, this is proved by the obtained T hitutng 4.176> 1.658 T table which means T count greater than T table. Likewise, the social environment has a significant influence on active students of Madrasah Aliyah Al Jazuliyah, this is confirmed by the obtained T hitutng 8.793> 1.658 T table which means that T count is greater than T table. And motivation and social environment together have a very strong and significant influence on students' entrepreneurial interest, highlighting the importance of these factors in fostering entrepreneurial intentions.Keywords: Social Environment, Interest in Entrepreneurship, Motivation.